Influence of SETS Science Learning Program Towards Scientific Literacy Improvement (Journal of Primary Education, 2019)
The purpose of this study was to determine the effect of SETS visionary science learning program in improving the students' scientific literacy in their energy material and changes. SETS visionary science learning program, students are expected to be able to integrate concepts that are being learned with everyday life, then applied in real life. This type of research is the Quasy Experimental Design research with nonequivalent control group design research design. This research was conducted in class III SDN 1 Kalikoa. The sample consisted of 72 students, the research sample was divided into two groups: the experimental class and the control class. Both groups were given a pretest to find out the students' initial abilities. The experimental class was treated with SETS visionary science learning programs and the control class was treated with conventional learning. After giving the treatment the two groups were given posttest. Data analysis techniques using independent sample t-test and N-gain. Based on the analysis test obtained the average difference for the control class is 70.86 and the experimental class 80.64. The results of this study are that there is a significant influence of SETS visionary science learning programs on improving the scientific literacy of students. The average increase in scientific literacy is 0.48 (medium category). The students' response to the learning is very good so that the SETS vision learning can be recommended to be applied in elementary schools.